Crypto-correction. (Economist, 2018)
The article reports on the falling market value of digital currencies in 2018. The price of bitcoin fell to 6,000 U.S. dollar while the total market capitalization of cryptocurrencies also dropped. The trend is attributed to hacking cases, fraud allegations and a growing regulatory backlash around the world. In response, several banks have banned customers from buying cryptocurrencies with their credit cards.